Sistem Rekomendasi Penerima Zakat Untuk Mustahiq Dengan Metode Simple Additive Weighting (SAW) - Alexander J P Sibarani; Muhammad Natsir Gayo (Jurnal Komputer Terapan, 2021)
Zakat in Islam is a cleanser from wealth. Apart from cleansing from wealth, zakat also eases the burden of mustahiq. In Indonesia, which is predominantly Muslim, the problem of zakat is an important matter to maximize its management which will later be useful for overcoming poverty problems. Jami Nurul Hikmah Mosque is a religious and social institution located in Tangerang City. The problem that is often encountered is the method in selecting mustahiq which is still using the manual method so that it often causes problems such as the length of the selection process and the occurrence of miscalculations causing inaccurate mustahiq selection results. In addition, the unavailability of access to information to see mustahiq who have entered the list of zakat recipients has resulted in mustahiq who have received zakat to receive assistance more than once a year. Assessment criteria in determining zakat recipient recommendations for mustahiq include looking at the status of residence, income, employment status, number of dependents, and family vehicle. To solve this problem, a recommendation system was built that could help zakat managers in distributing zakat to zakat recipients. The Simple Additive Weighting (SAW) method is used to calculate the value of the criteria to produce zakat recipient recommendations. With this system, zakat managers can provide recommendations for potential zakat recipients quickly and accurately.